Challenges in the enforcement of shariah criminal offences in Selangor: between perception and reality - Wan Muhammad, Ramizah; Abdul Hamid, Abdul Shukor; Thobroni, Abdul Rahman; Hussin, Nasimah (UPM Press, 2015)
The enforcement of Shari’ah criminal offences in Selangor has always been subjected to public scrutiny. The commission of selected Shari’ah criminal offences has been rigorously enforced against by the Religious Enforcement Division of the Department of Islamic Affairs. Alas, there are times that the manner in which the enforcement has been carried out has led to public criticism. This article studies the power of the enforcement officers, the modus operandi of enforcement and the challenges faced by the Selangor Religious Enforcement Division. Using a mixed mode of content analysis and personal observation, the article argues that there is still much that needs to be done to improve the image and modus operandi of the enforcement of Shari’ah criminal offences in Selangor specifically and in Malaysia generally.